Exploring the primary aim of ethics in good governance: maintaining compliance or striving for excellence and innovation - Awang Abd. Rahman @ Jusoh, Amilah (2018)
Principles of good governance from Islamic perspective has been generally monopolized by the legal perspective under the purview of the term of shari’ah. This paper aims to explore the role of ethics in Islam as the foundation of the principles. It will scrutinize the primary concern of ethics, is it observing the compliance to the good by merely playing a complementary roles to law, or achieving certain point of achievement of the institutions. The objective is achieved by scrutinizing the philosophy behind the Qur’anic verses related to human action and exploring the meaning of ethics as discussed by the Muslim ethicists. It is found that the primary aim of ethics is to strive for achieving the highest point of human performance, including the organizational excellent achievements through its concepts of obligation and sanction which involve the core values of ihsan, taqwa and amanah. The consequences of this are among others: ethics really initiate the culture of excellence and innovation, push the organization and institution for the best service or product. Hence, it is the responsibility of each institution to venture into the culture of excellence and innovation as part of good governance practices of Islam, and not limited to complying with certain rules.